The Essential Traits of Tourism Today: Values, Motivations and Trends - Matteo Montebelli; Massimiliano Vavassori (Symphonya, 2017)
Tourism is driven by tourists and a traveller behaviour that has evolved over time, driven by changes in society. Trips have become shorter, there are a progressive disintermediation and cross-contamination, and increasingly self-defining function as a time of personal realisation. Not just ‘where’ but also ‘how’ people travel is the key. The diverse motivations behind travel behaviour and holidays have gradually multiplied over the years and aspects traditionally considered of little or no relevance to tourism are gaining importance.